Penyuluhan Sunat Massal Ceria : Langkah Sehat Menuju Masa Depan di Kampus Universitas Sunan Giri Surabaya - Salwa Sabrina; Maulidia Ilham Fadilah; Nurul Arifin; Wakid Evendi; Terubus Terubus; Pratolo Saktiawan; Didit Darmawan; Muhammad Zakki; Adi Herisasono; Rommy Hardyansah; Muchamad Catur Rizky (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
The implementation of promoting circumcision practices, the method used in the activity is the ABCD (Asset Based Community Development) method. This ABCD method emphasizes community assets and strengths compared to their needs or problems. The mass circumcision counseling program